Acute hematogenous osteomyelitis in pediatric patients: epidemiology and risk factors of a poor outcome. Issue 4 (April 2020) - Popescu, Bogdan; Tevanov, Iulia; Carp, Madalina; Ulici, Alexandru
Objective: Acute hematogenous osteomyelitis (AHO) has declining incidence in developed countries. AHO can cause rapid destruction of bone that can lead to functional impairment or even death if misdiagnosed and not treated urgently. In this study, we aimed to identify the main factors that may lead to a poor outcome and to establish a profile of patients with AHO who might have a negative outcome. Methods: We conducted a retrospective single-center study including 94 patients with AHO, over a 10-year interval. Complete medical history including age at diagnosis, sex, socioeconomic status, symptoms, entry portal, pathogenic agent, location of infection, radiological features, treatment, and outcome were recorded. Results: Male predominance was observed, with boys from rural areas more prone to a poor outcome. This is likely because they are more exposed to trauma and do not have proper access to emergency medical care. Staphylococcus aureus was the most common etiologic agent, with 84 patients testing positive. Disease evolution was toward chronicity in patients diagnosed late. The most frequent complications were sepsis and pathological fractures. Conclusions: In our study, patients with negative outcomes were characterized by young age, repeated negative cultures, delayed surgery, rural residence, and male sex.